Proposta de um modelo de apoio a análise para desenvolvimento de produtos sustentáveis via desenvolvimento simultâneo de produto, processo e cadeia de suprimento - Silva, Luciano Auad da (Universidade do Vale do Rio dos Sinos, 2011)
This paper discusses economic, social and environmental issues from the perspective of sustainable product development in companies, and the impact of these products on the society that consumes and discards them after their useful life. Through the definitions of sustainability to supply chain, processes and products, a model to support analysis of development for sustainable products was proposed through a simultaneous development environment. The research methodology used is characterized by a qualitative exploratory approach, with a case study research strategy, combined with interviews with the facilitators and the use of a literature research in order to put the researcher into direct contact with what was written on the subject of research. Among various processes of product development, this study narrowed to the areas of research in planning, production and marketing of a product called sustainable, analyzing the impact of each step in relation to the sustainable vision. The case green ethylene, developed by braskem s/a, was the object investigated and analyzed in the study, and led to the formalization of a model to support analysis of development for sustainable products development through development in product, process and supply chain.
Keywords: Pesquisa e desenvolvimento; Produtos sustentáveis; Desenvolvimento simultâneo; Eteno Verde; Research and development; Sustainable products; Simultaneous development; Green Ethylene; ACCNPQ::Engenharias::Engenharia de Produção